Population pharmacokinetics of methylphenidate hydrochloride extended-release multiple-layer beads in pediatric subjects with attention deficit hyperactivity disorder - Teuscher, Nathan S (Drug Des Devel Ther, 2015)
A new multilayer-bead formulation of extended-release methylphenidate hydrochloride (MPH-MLR) has been evaluated in pharmacokinetic studies in healthy adults and in Phase III efficacy/safety studies in children and adolescents with attention deficit hyperactivity disorder (ADHD). Using available data in healthy adults, a two-input, one-compartment, first-order elimination population pharmacokinetic model was developed using nonlinear mixed-effect modeling. The model was then extended to pediatric subjects, and was found to adequately describe plasma concentration–time data for this population. A pharmacokinetic/pharmacodynamic model was also developed using change from baseline in the ADHD Rating Scale (ADHD-RS)-IV total scores from a pediatric Phase III trial and simulated plasma concentration–time data. During simulations for each MPH-MLR dose level (10–80 mg), increased body weight resulted in decreased maximum concentration. Additionally, as maximum concentration increased, ADHD-RS-IV total score improved (decreased). Knowledge of the relationship between dose, body weight, and clinical response following the administration of MPH-MLR in children and adolescents may be useful for clinicians selecting initial dosing of MPH-MLR. Additional study is needed to confirm these results.